2022
DOI: 10.1007/s00392-022-02033-y
|View full text |Cite
|
Sign up to set email alerts
|

Collateral effect of the COVID-19 pandemic on cardiology service provision and cardiovascular mortality in a population-based study: COVID-COR-LT

Abstract: Background Collateral damage of the COVID-19 pandemic on cardiovascular health is increasingly studied. This is a population-based study addressing multiple aspects of cardiovascular care during the pandemic in a country of Lithuania, in which pandemic waves were significantly different. Methods Data on cardiology outpatient care, hospitalizations and cardiovascular mortality in 2019 and 2020 were collected from Lithuanian nationwide administrative databases and registr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Third, adults in U.S. who are under Medicare age (generally under 65) have unequal access to health insurance, which may affect the access to health care and thus lead to an increase in mortality. Meanwhile, the elderly with cardiovascular diseases may actively seek outpatient care, whereas healthier young people may delay seeking care ( 37 ). In addition, the elderly still experienced the greatest absolute mortality and excess deaths remained persistent even in 2023 compared to the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…Third, adults in U.S. who are under Medicare age (generally under 65) have unequal access to health insurance, which may affect the access to health care and thus lead to an increase in mortality. Meanwhile, the elderly with cardiovascular diseases may actively seek outpatient care, whereas healthier young people may delay seeking care ( 37 ). In addition, the elderly still experienced the greatest absolute mortality and excess deaths remained persistent even in 2023 compared to the other two groups.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a survey of health care workers from 64 countries found that most felt that people with TB and HIV faced greater challenges accessing health services during the pandemic, with reduced mobility and health facility closures frequently stated as reasons [19]. While the pandemic's effects on TB-associated mortality have not yet become clear [20], increased deaths from cardiovascular disease [21,22], neonatal deaths [23], and deaths attributable to delays in accessing medical care during the pandemic [24] have been reported in various countries. Thus, it is an important lesson for future public health emergencies that changes to health system priorities and procedures should consider who may be harmed as well as who will benefit.…”
Section: Discussionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) pandemic carries a potential increase in the number of patients with cardiovascular (CV) diseases and in the individual risk of atherosclerotic cardiovascular disease (ASCVD). This may be the result of complications from the coronavirus infection itself [1], adverse lifestyle changes during the lockdowns and quarantine periods [2][3][4][5], and limitations in preventive, diagnostic, and therapeutic procedures due to changes in the organization of healthcare [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…However, the pandemic's effects on the population's health are not limited to the coronavirus infection. The restrictive epidemiological limitations and the reorganization of health care contributed to a decline in the availability of outpatient and inpatient treatment, a reduction in the effectiveness of primary and secondary prevention of CV diseases, and an increase in CV mortality [6,7]. In addition, epidemiological studies conducted on the Polish population indicate the limitation of physical activity in 43% of people [4]; increased food and snacks consumption in 34%-43% and 52% of people [4,5], respectively; and weight gain in 30% of respondents [5], which was secondary to isolation during the pandemic.…”
Section: Introductionmentioning
confidence: 99%